'Part of me already knew': the experiences of partners of people going through a gender transition process. Issue 12 (2nd December 2017) - Chester, Krystle; Lyons, Antonia; Hopner, Veronica
Abstract: Research has shown that the gender transition of one partner in a relationship can have a significant impact on the non-transitioning partner. This paper explores the experiences of former and current cisgender partners of people making a gender transition. Six participants were recruited via snowball sampling and took part in semi-structured interviews, which were transcribed and analysed using interpretative phenomenological analysis. Three superordinate themes were identified, namely: (1) the shared and ongoing process of learning about a partner's transgender identity; (2) changes in relationships; and (3) impact on self and identity. Findings highlight the constructed nature of gender and sexual identities, and the fluidity with which partners experienced these aspects of their lives. Future research could usefully explore the support needs of partners of transitioning people and the best ways to access and distribute this support.